“Gastrointestinal Microbiota in Children and Adults. Viruses and Bacteria”, an online conference of Scientiﬁc Society for the Study of Human Microbiome 14.11.2020 - A. I. Ulyanin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.